Strategi Pengembangan Usahatani Sayuran Organik Kelompok Tani Cepoko Mulyo Kabupaten Boyolali - Galih Seno Samodro; Yuliawati Yuliawati (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This research aims to: 1) analyze internal and external factors into strengths, weaknesses and threats and opportunities of farmers group Cepoko Mulyo in the development of organic vegetable farming, 2) Analyze and establish the main strategies that can be applied in the development of organic vegetable farming. The research was conducted on February to April 2018 in farmer group Cepoko Mulyo in Pandansari, Wonodoyo Village, Cepogo district, Boyolali regency of Central Java Province. The type of research used is descriptive research and the method used the survey method. Analysis of qualitative and quantitative descriptive data with IFE, EFE, IE, SWOT, and QSPM matrices. The result of the analysis shows that based on the IFE matrix the main strengths are vegetables with varying sizes of 0.287. The main weakness is the management of information systems that have not been good with a score of 0.172, while based on the EFE matrix the main opportunity is the association of organic farming with a score of 0.239 and the main threat is high competition level with other farms with a score of 0.234. Based on the QSPM analysis the suggested strategy is to cooperate with both central and local government in product marketing.